Adopting Cutting-edge and Pedagogical Teaching-learning Approaches to Facilitate the Teaching and Research Skills - Sannathimmappa, Dr. Mohan B. (Adopting Cutting-edge and Pedagogical Teaching-learning Approaches to Facilitate the Teaching and Research Skills, 2024)
The current medical education system places a strong emphasis on competency and requires students to develop superior lifelong learning abilities. Medical students must acquire impactful learning skills and behaviors to become more proficient future practitioners. The College of Medicine and Health Sciences (COMHS) in Oman has recently revised its medical curriculum for the undergraduate program, incorporating lifelong learning as a core competency in its updated regulations. Lifelong learning prioritizes the acquisition of metacognitive skills, the ability to learn independently, self-evaluation, and a thoughtful mindset. These qualities can be instilled in students by employing suitable instructional and innovative teaching and learning methods. This article discusses the characteristics of lifelong learning and the various instructional methods used in the Microbiology and Immunology course at COMHS to encourage lifelong learning in undergraduate medical students. The traditional method of teaching is being transformed with innovative teaching techniques. It enhances the skills to adapt modern teaching methods. It also encourages an independent thinking and creativity through experimental activities. Effective teacher must be able to deliver their knowledge using the most effective teaching methods and stay current in their area of expertise through continuous research. This learning skill sharpen the teaching and research skills of both new and experienced management teachers, researchers, and trainers.